2021
DOI: 10.1021/acs.jafc.1c04695
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Alleviates Aluminum Chloride-Induced Bone Impairment in Rats by Activating the TGF-β1/Smad Signaling Pathway

Abstract: Aluminum (Al)-induced bone formation and metabolism disorder through inhibition of the TGF-β1/Smad signaling pathway is one of the important mechanisms of bone impairment. Ginsenoside Rg3 (Rg3), a specific biological effector molecule, can provide protection to bones. Previously, we demonstrated that Rg3 can reverse aluminum chloride (AlCl3)-induced oxidative stress and metabolic disorder of bones; however, whether the TGF-β1/Smad signaling pathway is involved in it remains unclear. First, we found that Rg3 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There are primarily four steps involved in the process of bone formation: cell proliferation, cell differentiation, cell mineralization, and cell apoptosis. [32] The TGF-𝛽1/Smad2/3 pathway has a critical function in these four phases of bone formation. [32,33] TGF-𝛽1 controls the transcription of many genes involved in bone development, including Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…There are primarily four steps involved in the process of bone formation: cell proliferation, cell differentiation, cell mineralization, and cell apoptosis. [32] The TGF-𝛽1/Smad2/3 pathway has a critical function in these four phases of bone formation. [32,33] TGF-𝛽1 controls the transcription of many genes involved in bone development, including Smad2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum (Al)-induced disorders of bone metabolism are a significant cause of osteoporosis. The research concluded that Rb1 significantly reverses osteoblast viability and osteoblast growth regulators, inhibits oxidative stress, and attenuates histological damage to osteoblasts by AlCl3( Zhu et al, 2016 ), activating the TGF-β1/Smad signaling pathway is one of the mechanisms by which Rg3 alleviates Al-induced bone damage ( Song et al, 2021 ). Song et al (2020) reported that Rg3 effectively alleviated AlCl3-induced osteoporosis by increasing the mRNA expression of transforming growth factor-β1, bone morphogenetic protein-2, insulin-like growth factor I, and core binding factor α1 to promote growth regulators and attenuate Al accumulation.…”
Section: Effects Of Ginsenosides On Metal-induced Toxicitymentioning
confidence: 99%
“…For example, TGF‐β overexpression is revealed to facilitate tendon‐bone healing after ACLR using BMSCs via the TGF‐β/MAPK pathway 12 . The TGF‐β1/Smad signaling is inhibited in the Aluminum Chloride‐induced bone impairment in rats, and Ginsenoside Rg3 can attenuate the structural damage and enhance the acitivity and differentiation of the osteoblasts via the activation of the TGF‐β1/Smad signaling 13 . Moreover, a study has indicated that the MEK /ERK and p38 MAPK signalings may directly interact with the Smad pathways to regulate TGF‐β1‐induced chondrogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…12 The TGF-β1/ Smad signaling is inhibited in the Aluminum Chloride-induced bone impairment in rats, and Ginsenoside Rg3 can attenuate the structural damage and enhance the acitivity and differentiation of the osteoblasts via the activation of the TGF-β1/Smad signaling. 13 Moreover, a study has indicated that the MEK /ERK and p38 MAPK signalings may directly interact with the Smad pathways to regulate TGF-β1-induced chondrogenesis. 14 Additionally, TGF-β1 can directly induce the murine BMSC osteogenic differentiation in vitro, 15 and TGF-β1 produced by BMSCs facilitates the bone regeneration and repair, which may deepen the understanding of the underlying mechanism of BMSCs-based therapy.…”
mentioning
confidence: 99%